2014
DOI: 10.1093/fampra/cmu038
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems in undocumented and documented migrants: a survey study

Abstract: UM had less consultations with their GP, and in these consultations, less mental health problems were registered. UM were referred less to psychologists but more often to psychiatrists. GPs are advised to explore and register mental health problems more actively in UM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 7 publications
2
31
1
2
Order By: Relevance
“…Although the prevalence of mental health problems, such as post-traumatic stress disorder, depression and anxiety is high among UMs in the Netherlands, 22 it is unclear from primary healthcare data to what extent professional care is responding to these needs. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of mental health problems, such as post-traumatic stress disorder, depression and anxiety is high among UMs in the Netherlands, 22 it is unclear from primary healthcare data to what extent professional care is responding to these needs. 23 …”
Section: Introductionmentioning
confidence: 99%
“…As they all practised in the main areas where many UMs were residing, we think the findings of this study are representive of the Dutch context. The majority of these GPs participated in an earlier survey study [ 13 ], and in this study we showed that their undocumented patients represented the general UM population in the Netherlands.…”
Section: Strenghts and Limitations Of The Studymentioning
confidence: 57%
“…However, despite the above-mentioned rights of UMs to obtain health care and the possible reimbursement for health care professionals (8), there are contradictory reports of the levels of mental health problems presented, recorded, and treated in primary care [ 11–13 ]. While one study showed that mental health problems were frequently presented in primary care [ 11 ], other studies showed low recording rates of mental health problems and low prescription rates of psychotropics [ 12 , 13 ]. These studies indicate a gap between the high prevalence of mental health problems presented by UMs and the low recording of these problems by GPs.…”
Section: Introductionmentioning
confidence: 99%
“…The finding of medication-based treatment being easier to achieve than psychotherapeutic treatment was likewise described by the Castañeda study 16. A study from the Netherlands also found that undocumented people were referred significantly more often to psychiatrists than psychologists, probably because psychologists would not receive any reimbursement for conceivable psychotherapeutic care 52. For Greece, problems with drug prescription and referrals to mental health institutions due to lack of reimbursement were also described 53.…”
Section: Discussionmentioning
confidence: 87%